Becoming parents. Family education and birth preparation paths - Catarsi, Enzo (Rivista Italiana di Educazione Familiare, 2011)
The birth of a child is a crucial event in men’s and women’s life, since it implies establishing new parental identities, besides changing the way roles and relationships within the family household are planned and defined. In this view, birth, especially in the case of the first-born, results to be “destructuring”, as setting new roles both in the couple and in the whole relatives’ family. It is also for this reason that the article argues that research on the topic of birth cannot be delegated just to medical science, but must also be acquired by family education. One of the research perspectives that we can follow is the one that uses parental writings and autobiographical narratives. The article stresses then the new parents’ need of support, and in this regard it proposes “birth preparation paths” as an experience of family education. On these occasions useful information could be provided on suckling, first bath and other technical aspects, or on customized educational instructions. Among the goals, helping future parents start identifying in the role their parts by training them to sympathy and affection is a major one.